Application Of Internal Quality Evaluation And Audit As A Performance Measurement Tool In Islamic Higher Education In North Sumatra - Dedi Amrizal; Yusriati Yusriati (Proceeding International Seminar of Islamic Studies, 2019)
Building a quality culture is not as easy as we imagine. One of the quality criteria that has been entrenched is the ongoing evaluation of quality and audit quality as a means of measuring performance. Quality evaluations and audits that take place in several Islamic tertiary institutions in Sumatra are modest and rarely followed up. In fact this is an important stage in measuring performance in every tertiary institution from the lowest level to the highest level. This study aims to (1) find out the implementation of quality evaluations and audits in Islamic tertiary institutions (2) explain the constraints of conducting quality evaluations and audits in Islamic tertiary institutions; (3) analyze the reasons for not following up on the quality evaluation and audit that has been carried out. This study uses a descriptive research method with a case study approach to prove that the implementation of internal quality evaluations and audits in several Islamic tertiary institutions in North Sumatra Province has been carried out or not. Furthermore, through this method, there will also be a follow-up to what the Islamic tertiary institution did from the evaluation and audit findings. The results showed that the evaluation of quality management and quality management audits in most Islamic tertiary institutions were still not going well. If someone has already carried out a quality evaluation and audit, it appears that the follow-up has not been carried out and followed. Two the causes of this happening, namely the belief that the evaluation and audit have not been perfect so that it is not appropriate to be used as a measurement of actual performance. Furthermore, he did not know what else to do if an evaluation or quality audit was carried out.